Virtual Reality-Based Simulation Design for Hazardous and Toxic Waste Management in the Cement Industry - Denaldi Rananda Saputra; Mega Cattleya PA Islami (Yayasan Kita Menulis, 2025)
Businesses with activities that impact the environment must conduct environmental protection and management for the waste and emissions resulting from their operations. Provisions regarding this matter are stated in Government Regulation Number 22 of 2021. Environmental management must be appropriate according to the type of waste produced, including hazardous and toxic waste. Hazardous and toxic waste has specific methods for storage and management, as detailed in the Regulation of the Minister of Environment and Forestry Number 6 of 2021. However, many companies still violate these regulations and must understand the proper storage techniques for hazardous and toxic waste. Therefore, with the advancement of current technology, we can create interactive technology for education and awareness, one of which is virtual reality-based simulation. Hence, the researcher designed a virtual reality-based simulation for hazardous and toxic waste management in the manufacturing industry.